China's post-WTO intellectual property system: assessing compliance with the TRIPS agreement - Thomas, Kristie (2008)
This thesis examines the system of intellectual property (IP) protection in contemporary China. The IP system has undergone a series of dramatic reforms in recent years, particularly as a result of China's accession to the World Trade Organisation. From December 2001, China is now committed to comply with the WTO Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS). However, despite implementing TRIPS provisions into domestic legislation, infringements are still prevalent and criticism of the IP system continues.